2018
DOI: 10.2340/00015555-2992
|View full text |Cite
|
Sign up to set email alerts
|

Sub-optimal Application of a High SPF Sunscreen Prevents Epidermal DNA Damage in Vivo

Abstract: The cyclobutane pyrimidine dimer (CPD) is a potentially mutagenic DNA photolesion that is the basis of most skin cancers. There are no data on DNA protection by sunscreens under typical conditions of use. The study aim was to determine such protection, in phototypes I/II, with representative sunscreen-user application. A very high SPF formulation was applied at 0.75, 1.3 and 2.0 mg/cm2. Unprotected control skin was exposed to 4 standard erythema doses (SED) of solar simulated UVR, and sunscreen-treated sites t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Additionally, sunscreen application is often considerably less than the amount recommended (2 mg/cm 2 ) by the U.S. Food and Drug Administration (FDA) (U.S. Food and Drug Administration, 2012). A study among beachgoers (Lademann et al, 2004) found that volunteers typically applied only 10% of the recommended amounts, with the ears and top of the feet mostly remaining unprotected and a recent study (Young et al, 2018) found that sunscreen applied at 0.75 mg/cm 2 , was not effective in reducing DNA damage from UVR exposure. Currently, the FDA requires sunscreen labeling stating that sunscreen should be used in combination with other sun protective measures, such as the use of shade or protective clothing (U.S. Food and Drug Administration, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sunscreen application is often considerably less than the amount recommended (2 mg/cm 2 ) by the U.S. Food and Drug Administration (FDA) (U.S. Food and Drug Administration, 2012). A study among beachgoers (Lademann et al, 2004) found that volunteers typically applied only 10% of the recommended amounts, with the ears and top of the feet mostly remaining unprotected and a recent study (Young et al, 2018) found that sunscreen applied at 0.75 mg/cm 2 , was not effective in reducing DNA damage from UVR exposure. Currently, the FDA requires sunscreen labeling stating that sunscreen should be used in combination with other sun protective measures, such as the use of shade or protective clothing (U.S. Food and Drug Administration, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that sunscreens can prevent the accumulation of thymine dimers from repeated daily suberythemal SSR exposure . We have also shown that a high‐SPF sunscreen can prevent DNA damage caused by acute and repeated high‐dose SSR exposure . However, there are very limited data on the relationship between SPF and DNA protection factor.…”
Section: Discussionmentioning
confidence: 99%
“…Sunscreens are effective because they attenuate solar UVR. Their use can inhibit cyclobutane pyrimidine dimers (CPDs) [68], sunburn and skin cancer [69]. The sun protection factor (SPF) of a sunscreen is primarily an index of its ability to attenuate UVB [70].…”
Section: Skinmentioning
confidence: 99%